The digestibility, ruminal fermentation and methane product of Cajanus cajan forage as a concentrate substitute in goats - Abidinsyah, D. A.; Suyub, I. B.; Jusoh, S.; Yaakub, H. (Diponegoro University, 2024)
Sixteen local goats (9.3 kg bodyweight) were assigned to different groups based on a 21-day completely randomized design and fed with Cajanus cajan forage. The objectives of the study were to evaluate digestibility, ruminal fermentation and estimation of methane production of C. cajan forage as a concentrate substitute in goats. Four treatments were used in the feeding trial: T0CC = 100% concentrate; T25CC = 75% concentrate + 25% C. cajan forage; T75CC = 25% concentrate + 75% C. cajan forage; and T100CC = 100% C. cajan forage. Ruminal fluid was collected during the last week of the experiment after feeding and used to determine pH, ammonia, partial VFA, and methane gas production. Dry matter intake, nutrient digestibility, and total body weight gain were not significantly different (P>0.05) between goats fed with T0CC and T25CC. The addition of C. cajan forage to the diet did not significantly (P>0.05) affect pH, ammonia content, and total VFA but influenced acetate, propionate, butyrate, AP, and estimated CH4 produced. Hence, C. cajan forage may replace 25% of concentrates in a rice straw-based diet for goats.